Impact of chemical stochastics in extreme ultraviolet photoresists on the pattern quality - Jianing Li; Haoyuan Li (AIP Advances)
Stochastic issues have been recognized as a major limiting factor in improving the pattern quality in extreme ultraviolet (EUV) lithography. These stochastic factors include photon shot noise (PSN) and chemical noise within the photoresist. While the impact of the former has been relatively well-established, the influence of the latter was largely unclear. Here, we apply high-throughput Monte Carlo simulations to investigate the chemical stochastics on pattern quality, focusing on the vertical photoacid generator (PAG) and base distribution and their aggregation. Our results indicate that the non-uniform vertical distribution of the PAG and base leads to the bottom residue. Suppressing the micro-aggregation of the PAG and base or limiting each aggregate containing 3 or fewer PAGs and 1 base (e.g., through chemical bonds) minimizes the negative impact of chemical stochastics on pattern quality. Increasing the dose and PAG concentration can effectively mitigate the negative impact of chemical stochastics on pattern quality, suggesting that PSN and chemical stochastics in EUV photoresist are intrinsically connected and need to be considered comprehensively. These findings serve as a valuable theoretical reference for the rational design of EUV photoresists.